Influence of Classroom-Based Experiential Learning Activities on Learners’ Classroom Performance and Learning Engagement in Public Elementary Schools of Guinobatan West District, Schools Division of Albay - Suarez, Rechelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of classroom-based experiential learning activities on the classroom performance and learning engagement of Grade 4 learners in public elementary schools in Guinobatan West District, Schools Division of Albay, for School Year 2025–2026. It was anchored on Self-Efficacy Theory, Progressivist Theory, Constructivism, and the researcher’s Learner-Centered Experiential Learning Theory. Using a descriptive-correlational research design, the study involved thirty Grade 4 teachers as respondents. Data were gathered through a researcher-made questionnaire checklist, supplemented by informal interviews, documentary analysis, library techniques, and internet-based research. Frequency distribution, percentage, weighted mean, five-point rating scale, and Spearman Rank-Order Correlation were used to analyze the data. Findings showed that Grade 4 learners participated in classroom-based experiential learning activities to a “sometimes” extent, with an average mean of 3.30. The influence of these activities on classroom performance was “much evident” with a mean of 3.82, while their influence on learning engagement was also “much evident” with a higher mean of 4.06. Overall, experiential learning activities supported motivation, participation, comprehension, practical application, collaboration, communication, critical thinking, and problem-solving. However, the computed Spearman rho value of 0.04 showed no significant correlation between classroom performance and learning engagement. Based on the findings, Classroom-Based Experiential Learning Lesson Exemplars were developed to support the effective implementation of experiential learning activities. The study supports SDG 4, Quality Education, by promoting meaningful, learner-centered instruction, and SDG 17, Partnerships for the Goals, by recognizing the role of teachers, school heads, parents, stakeholders, and future researchers. Its sustainability impact lies in strengthening instructional planning, teacher facilitation, learner participation, and school-community support for improved basic education outcomes.
Keywords: Classroom Performance; Classroom-Based Experiential Learning; Grade 4 Learners; Learning Engagement; Learner-Centered Instruction; Lesson Exemplars; Public Elementary Schools; SDG 4; SDG 17